Influence of technological pedagogical content knowledge (TPACK) and ICT utilization among pre-service teachers - Musa, Umar; Mahmud, Rosnaini; Mohd Daud, Shaffe; Ab. Jalil, Habibah (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
ICT has become a key attention and concentration in the education sector, that improved the method of retrieving information and significantly changes the methods of the contact between learners and their peers, as well as between learners’ and means of information and even students-instructor. This paper discussed TPACK and its dimensions, and their influence on pre-service teachers use of ICT.